El análisis de la Variación Estacional en medicina - Marrero, Osvaldo (2005)
This is a survey of recent methods for the analysis of seasonal variation in medical research. These methods are effective even when the data show small amplitude and the sample size is small, two characteristics that are often present when one analyzes medical data for seasonal variation. The methods deal with both cases: one group and multiple groups. Also, these methods can be used to analyze different types of seasonal variation. Real-data examples are used to illustrate the application of these techniques.